2013
DOI: 10.1167/iovs.12-10888
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat-Induced Retinal Degeneration Is Exaggerated in CX3CR1-Deficient Mice and Is Associated with Increased Retinal Inflammation

Abstract: PURPOSE.To investigate the role of the Fractalkine receptor CX3CR1 pathway in oxidative insults-mediated retinal degeneration and immune activation. RESULTS. Intravitreal injection of paraquat (0.75 lM) resulted in acute retinal capillary nonperfusion within 2 days, which improved from 4 days to 4 weeks postinjection (p.i.). Panretinal degeneration was observed at 4 days p.i. and progressed further at 4 weeks p.i. In the absence of CX3CR1, retinal degeneration was exaggerated and was accompanied by increased T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…The neuronal cell bodies unaffected by Met treatment were most likely not expressing the Ntr transgene. Our TEM analysis revealed signs of degeneration in the neuronal cell bodies of Met-treated Ntr larvae consistent with previous reports that showed neuronal membrane disruption in a toxin-induced axon degeneration mouse model, and with those from a drosophila mutant with disrupted axonal transport leading to axon degeneration [58], [59]. Thus, the results from these TEM studies support the observations made at a macro level with epifluorescence microscopy.…”
Section: Resultssupporting
confidence: 91%
“…The neuronal cell bodies unaffected by Met treatment were most likely not expressing the Ntr transgene. Our TEM analysis revealed signs of degeneration in the neuronal cell bodies of Met-treated Ntr larvae consistent with previous reports that showed neuronal membrane disruption in a toxin-induced axon degeneration mouse model, and with those from a drosophila mutant with disrupted axonal transport leading to axon degeneration [58], [59]. Thus, the results from these TEM studies support the observations made at a macro level with epifluorescence microscopy.…”
Section: Resultssupporting
confidence: 91%
“…A commonly used molecule to mimic the effects of oxidative stress in the CNS is paraquat, 1,1′-Dimethyl-4,4′-bipyridinium dichloride, which generates oxygen free radicals through redox cycling and NADPH oxidase regulation (Corasaniti et al, 1998; McCormack et al, 2005; Cingolani et al, 2006; Chen et al, 2013). In this study, we used paraquat (PQ) to induce acute oxidative stress in the retina.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study demonstrated that inflammatory cytokines protect against oxidative stress induced degeneration of the RPE (Chen et al, 2013; Juel et al, 2013). TLR3 signaling within astrocytes leads to secretion of neuroprotective mediators and promotes tissue repair responses (Bsibsi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…High Cx3Cr1 expression has been associated with a functionally distinct class of monocytes with immune patrolling activity and with a molecular profile of macrophage differentiation resembling alternative activation (18, 19). Loss of Cx3Cr1 results in retinal degeneration in response to several stimuli and is associated with pro-inflammatory activation of immune cells (9, 14, 59). Thus we hypothesized that loss of Cx3Cr1 could be an effective way to impair MANF-induced alternative activation.…”
Section: Manf-dependent Modulation Of Immune Cell Phenotypes Mediatesmentioning
confidence: 99%